Elemental bioimaging and speciation analysis for the investigation of Wilson's disease using μXRF and XANES. Issue 7 (21st March 2016) - Hachmöller, Oliver; Buzanich, Ana Guilherme; Aichler, Michaela; Radtke, Martin; Dietrich, Dörthe; Schwamborn, Kristina; Lutz, Lisa; Werner, Martin; Sperling, Michael; Walch, Axel; Karst, Uwe
Abstract : A liver biopsy specimen of a Wilson's disease patient was analyzed by means of micro-X-ray fluorescence (μXRF) and X-ray absorption near edge structure spectroscopy (XANES). Abstract : A liver biopsy specimen from a Wilson's disease (WD) patient was analyzed by means of micro-X-ray fluorescence (μXRF) spectroscopy to determine the elemental distribution. First, bench-top μXRF was utilized for a coarse scan of the sample under laboratory conditions. The resulting distribution maps of copper and iron enabled the determination of a region of interest (ROI) for further analysis. In order to obtain more detailed elemental information, this ROI was analyzed by synchrotron radiation (SR)-based μXRF with a beam size of 4 μm offering a resolution at the cellular level. Distribution maps of additional elements to copper and iron like zinc and manganese were obtained due to a higher sensitivity of SR-μXRF. In addition to this, X-ray absorption near edge structure spectroscopy (XANES) was performed to identify the oxidation states of copper in WD. This speciation analysis indicated a mixture of copper(i ) and copper(ii ) within the WD liver tissue.